A New Species of Anticheta (Diptera: Sciomyzidae) from Mexico - Pote, Spencer L.; O’grady, Patrick (Zootaxa, 2023)
Anticheta patzcuaroensis Pote, new species (Diptera: Sciomyzidae), from Lake Pátzcuaro, Michoacán, Mexico, is described and illustrated. The most recent key to the genus Anticheta Haliday in the Nearctic region is edited to include the new species. Information is given about the Sciomyzidae holdings in the Cornell University Insect Collection.